GASOLINE GENERATOR WITH CAVITATION FUEL MIXTURE PREPARATION - AFTANAZIV, IVAN; SHEVCHUK, LILIA; STROHAN, ORYCA; STRUTYNSKA, LESYA; SHEVCHUK, SOFIA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The results of an experimental study of the effectiveness of cavitation treatment of a fuel mixture based on A-95 gasoline and distilled water for internal combustion engines of electric generators are described. Cavitation treatment of this fuel mixture with a percentage ratio of water / gasoline of 17/83% allows to increase the saving of expensive gasoline by 15-20% when operating gasoline engines of household and industrial generators. At the same time, the engine power is reduced by only 6÷7% due to the cavitation treatment of the water-gasoline fuel mixture. A description of the design scheme of the electromagnetic vibrating mixer-cavitator created for the cavitation treatment of water-gasoline fuel is given. Its use will allow not only to save fuel during the operation of electric generators, but also to increase the degree of completeness of combustion of their water-gasoline fuel mixture, that is, it will contribute to the improvement of environmental ecology. The proposed improved technological scheme for powering the cylinders of the internal combustion engine of the electric generator with cavitationally treated water-gasoline fuel includes supplementing the traditional gasoline supply network with an additional water supply network with a water storage tank and an electromagnetic vibrating cavitator for mixing the water-gasoline mixture. Experimental studies have established the optimal operating modes of the vibrating cavitation mixer of the fuel mixture. The highest quality of mixing water with gasoline is ensured when the amplitude of oscillations of the cavitation disturbers is in the range of 0.4-0.5 mm at the frequencies of their oscillations of 45-47 Hz. To form a water-fuel mixture, the technological scheme of the fuel supply of the electric generator is additionally equipped with a water supply system. The water supply system includes a water storage tank, a filter for its purification, a supply pipeline and a vibrating cavitation mixer of water with gasoline. Such additional equipment of the electric generator with a water supply system increases its cost by only 4-5%. With daily operation of electric generators of the Konner and Sohner KS15-1E ATSR model with a capacity of 12.5 kW for 5-6 hours, the costs of its arrangement will pay off in approximately half a calendar year.